Putusnya Perkawinan karena Kematian sebelum Terjadinya al-Dukhūl; Masa ‘Iddah dan Kaitannya dengan Kaedah Taqdīm al-Naŝála al-Qiyās - Arif Marsal (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2017)
Qiyas which issahih is hujjah that has been accepted in the stipulation of law. The position of Qiyas in fuqaha’s understanding is as the source of law after Quran , Hadits and Ijma’. Nonetheless sometimes in practice,some of the fuqaha’ do not search and steep in detail dalil before they actually go inside the qiyas’s method in istidlal.The issue of the divorcebecause of the quietus before the occurance of jima’(qabla al-dukhul) is becoming part the writer’s object to be analized wether the effect is the same and it can be qiyas with the divorce (life divorce), which both of them occured before the jima’ (al-dukhul). The writer’s found that the Qiyas can not be prevailed in this issue because it is found that there’s a specialite dalil from nash. Which elucidates each of the law and it specifies that nash come first compare to the notion/opinion and lid for the ijtihad and qiyas toward the issue of the nash that has been described.